2018
DOI: 10.1182/bloodadvances.2017015396
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide consolidation benefits patients with CLL receiving chemoimmunotherapy: results for CALGB 10404 (Alliance)

Abstract: Prior to novel targeted agents for chronic lymphocytic leukemia (CLL), the best chemoimmunotherapy regimen in patients with non-del(11q) disease was unclear. The role of lenalidomide was also not defined. This phase 2 study randomized 342 untreated patients with non-del(11q) CLL requiring therapy to fludarabine plus rituximab (FR; n = 123), FR plus lenalidomide consolidation (FR+L; n = 109), or FR plus cyclophosphamide (FCR; n = 110) and compared 2-year progression-free survival (PFS) rates of each to the hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…To limit toxicity, lenalidomide was evaluated as maintenance therapy after chemoimmunotherapy. Two randomized clinical trials (CLL M1 and CALGB10404) showed that lenalidomide maintenance reduced disease progression [83,84]. However, three unexpected cases of B-ALL in the lenalidomide maintenance arm resulted in the termination of the CLL M1 study [83].…”
Section: Combining Btk Inhibitors With Immunomodulatory Drugsmentioning
confidence: 99%
“…To limit toxicity, lenalidomide was evaluated as maintenance therapy after chemoimmunotherapy. Two randomized clinical trials (CLL M1 and CALGB10404) showed that lenalidomide maintenance reduced disease progression [83,84]. However, three unexpected cases of B-ALL in the lenalidomide maintenance arm resulted in the termination of the CLL M1 study [83].…”
Section: Combining Btk Inhibitors With Immunomodulatory Drugsmentioning
confidence: 99%
“…In a clinical trial for patients with symptomatic CLL (NCT00602459), lenalidomide was combined with fludarabine and rituximab. Results showed that a lenalidomide consolidation after chemoimmunotherapy is tolerated and extends progression-free survival and overall survival [192]. Thus, clinical trials are ongoing to test the safety of lenalidomide as maintenance therapy for CLL patients after chemotherapy (NCT00774345), and its use as first-line treatment in combinations with bendamustine and rituximab (NCT01400685).…”
Section: Immunomodulatory Drugs (Imids)mentioning
confidence: 99%
“…Interestingly, it has been shown that immune escape of CLL can be achieved by various means, notably by those interfering with the formation or the function of the lytic IS (25)(26)(27)(28)(29). Lytic IS formation of CD8 + T cells and NK cells with CLL cells can be rescued in part by drug treatments, such as lenalidomide or blocking antibodies, or can even be bypassed by infusion of genetically modified cytotoxic lymphocytes which do not rely on MHC-mediated antigen presentation as they form a non-classical IS (30)(31)(32)(33)(34)(35)(36). Nevertheless, toxic side effects or acquired resistance against these new therapeutic options have been reported and result in disease progression (37,38).…”
Section: Introductionmentioning
confidence: 99%